THE RELATIONSHIP OF PHYSICAL QUALITIES AND MOTOR SKILLS IN YOUNG ATHLETES - Turdimuratov J. A.; Utegenov J. J. (Journals Park Publishing, 2024)
The article presents data related to the substantiation of the training system for young athletes, the identification of patterns of age-related development of physical qualities in children, adolescents, boys and girls specializing in various sports.
Keywords: Motor actions, education of physical qualities, movement training, development of physical qualities, specifics of sports training, features of growth and development.